Analisis Kualitas Pelayanan Terhadap Tingkat Kepuasan Pelanggan pada Borma Toserba Antapani Bandung - Utami Amadea Soetardjo (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this study is to find out how much influence service quality has on customer satisfaction at Borma Toserba Antapani Bandung, and also to find out the constraints and efforts that can be made. The number of samples studied was 93 people taken from the number of visitors for the period January - December 2021. The research method used is quantitative. Then using percentage calculation techniques, validity test, reliability test, normality test, simple linear regression, and t-test. The results of the study show that the percentage calculation rate regarding service quality is 91.82% indicating service quality to customer satisfaction is included in the very good category. The remaining percentage gap (gap) is 8.18% then a significance level of 0.00 <0.05 means that the x variable has a significant effect on the y variable. The value of R Square is 0.593 which means 59.3% of service quality affects customer satisfaction. With the rest, it can be influenced by factors that are not examined with a moderate degree of correlation. It can be concluded that the company has made efforts to improve service quality but the problem is in the number of employees who are not in balance with the number of customers. Thus reducing the level of customer satisfaction. Efforts are taken to maximize customer satisfaction by increasing the number of employees.